RESPON SISWA TERHADAP MEDIAE-LEARNING BERBASIS WEB BLOGMATERI SISTEM PERNAPASAN KELAS VIII SMP - Mandayu, Astody Gusta; Putri Panjaitan, Ruqiah Ganda; Titin, Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to determine the students responses of e-learning media based web blog on the respiratory system material on class VIII SMP Kristen Immanuel II Kubu Raya. The form of research isResearch and Development (R&D) method with ADDIE model. The sample in this research are the students of class VIII C consisting of 39 students.Instruments are used a student response questionnaire to find out the student's response to the e-learning media based web blog on respiratory system material. The response of students classified into three category, namely responses that are cognitive, affective and conative. The students will response questionnaire consists of 21 statements, 11 positive statements and 10 negative statements. The cognitive response reached an average score of82,52% in positive categories, affective responses achieved an average percentage of 83,23% in positive category, and the conative response reached an average percentage of83,33% in positive category. It can be concluded that student’s responses are positive in the cognitive, affective and conative responses.Keywords: E-learningMedia, Web blog, Student’s Responses, Respiratory System